FE2+-MG FRACTIONATION BETWEEN ORTHOPYROXENE AND SPINEL: EXPERIMENTAL CALIBRATION IN THE SYSTEM - Liermann H.P.; Ganguly J. (My University, 2003)
We have determined the equilibrium Fe2+–Mg fractionation between orthopyroxene and spinel in the ferromagnesium system at 0.9–1.4 GPa, 850–1,250°C, and also as a function of the Cr/Al ratio of spinel at 1.24 GPa, 1,000°C. At each P–T condition, the equilibrium value of the distribution coeﬃcient, KD(Fe–Mg), was constrained by experiments with crystalline starting mixtures, and approaching from both higher and lower initial values. The experimental data have been cast, within a thermodynamic framework, in the form of a geothermometer in the system FeO–MgO–Al2O3–Cr2O3–SiO2 (FMACrS). Using the data of O’Neill and Wall (1987) on the thermodynamic properties of Fe3+ and Ti4+ bearing spinels, we extended the thermometric formulation to account for the effect of these components. However, practical application of the extended formulation is beset with the problem of accurate determination of Fe3+ content of natural minerals. Using published data, the thermometric formulation in the FMACrS system has been applied to a number of natural assemblages that have small Fe3+ content. The retrieved temperatures are generally higher, on the average by ~60°C, than those obtained from the olivine-spinel Fe2+–Mg exchange thermometer of O’Neill and Wall, as modiﬁed by Ballhaus et al. (1991), but are more compatible with the original temperature estimates by the authors of the publications. The smaller Fe2+–Mg interdiﬀusion coeﬃcient, D(Fe–Mg), in orthopyroxene compared with those in both olivine and spinel is expected to yield higher temperatures from orthopyroxene–spinel than from olivine–spinel thermometry.
Keywords: Orthopyroxene; Spinel